Technika biegu na dystansie ultramaratonu - Ratkowski, W.; Aschenbrenner, P.; Erdmann, W. S. (Medycyna sportowa, 2003)
Background. The main purpose of this work is to evaluate the technique of locomotion (technique of pace) during long-term run in the marathon. Material and methods. Three sport runners, participants of National Marathon, have been examined. The technique of pace on selected distances of the 100 km run, have been recorded twice. Colected meterial has been analized from the biomechanical point of view. Results. During 100 km marathon, it is possible to show, the differences in the angles determinating locomotion pattern. Conclusions. The exortion during long-term run, represents itself in changing efectivenes of particullar groups of muscles, responsible for the locomotion.